Diques clásticos na formação corumbataí (p) no nordeste da bacia do paraná, SP: Análise sistemática e significações estratigráficas, sedimentológicas e tectônicas - Perinotto, José Alexandre de Jesus [UNESP]; Etchebehere, Mario Lincoln de Carlos; Simões, Luiz Sérgio Amarante [UNESP]; Zanardo, Antenor [UNESP] (My University, 2008)
This paper aims to present the results of systematic survey on clastic dykes in the Corumbataí Formation (Permian), in the northeast region of the State of São Paulo. Besides this, the paper analyses genetic aspects of those features as well as their stratigraphic and sedimentologic implications in terms of geologic evolution of the northeastern Paraná Sedimentary Basin during Permian times. The field works had been developed in 3 main Corumbataí Formation outcrops (2 road cuts and a quarry) supposed to show the most important clastic dikes occurrences in the studied area. Basically, the sedimentary intrusions are formed by fine sand or silt size particles and had penetrated host rocks as near-vertical, centimeter thick, dykes (most common form) or as horizontal sheets, forming clastic sills (subsidiary form), both with variable geometric forms and dimensions. A lot of dyke walls show undulations suggesting pre-diagenetic clastic intrusions, probably near the ancient depositional surface. Almost all intrusions occur in the superior third portion of the Corumbataí Formation and some similar features seem to appear in the adjoining superposed Pirambóia Formation base. In this article the authors defend a seismic origin hypothesis for the clastic intrusions. It is important to mention that clastic intrusions tend to occur linked to expressive seismic events, with magnitude upper to 5. The analysis of isopach maps of the Permian and Mesozoic units of the Paraná Sedimentary Basin in the study area suggests a depositional system changing, from epicontinental sea conditions to shallow platform and, finally, to coastal deserts. Probably, this environmental change was driven by regional uplift accompanied by seismic events. It is possible that ancient seismicity triggered liquefaction processes and the resulting clastic intrusions. In this sense, those clastic features might be properly namedseismites.

Este trabalho tem como objetivo apresentar os resultados de um levantamento sistemático dos diques clásticos encontrados na Formação Corumbataí, na região nordeste do Estado de São Paulo. Busca-se, também, explorar aspectos relativos à gênese e às significações estratigráfico-sedimentológicas dessas estruturas, bem como de suas implicações estratigráficas, tectônicas e evolutivas para esta porção da Bacia Sedimentar do Paraná e de seu registro geológico. Os trabalhos de campo foram desenvolvidos em 3 principais afloramentos (dois cortes de estrada e uma pedreira), que congregam as mais importantes ocorrências de diques na área de estudo. Os diques se mostram, regra geral, constituídos de material arenoso ou síltico-arenoso, que penetram rochas adjacentes, tanto na vertical, formando os chamados diques clásticos (predominantes), como, por vezes, na horizontal formando sills (subordinados). Os diques presentes nessa unidade estratigráfica apresentam-se sob diferentes formas e dimensões, e encontram-se restritos aos estratos superiores da Formação Corumbataí. As paredes dos diques mostram deformações que indicam efeitos de compactação, sugerindo que os diques se intrudiram nos sedimentos encaixantes em situação pré-diagenética, provavelmente nas proximidades da superfície pretérita. Defende-se, neste artigo, a hipótese de uma origem sísmica para as intrusões clásticas. Essas estruturas tendem a ocorrer a partir de sismos de magnitude superior a 5, o que implica em eventos expressivos, recorrentes durante a deposição do terço superior da Formação Corumbataí, avançando, inclusive, para a porção basal da Formação Pirambóia. A análise de mapas de isópacas das unidades permianas e mesozóicas abrangendo a porção nordeste da Bacia do Paraná sugere um recuo das condições marinhas epicontinentais para ambiente plataformal raso e, finalmente, desertos costeiros. Este soerguimento tectônico poderia se fazer acompanhado de sismicidade expressiva, registrada como as intrusões aqui tratadas – que poderiam ser designadas, assim, “sismitos”. Palavras-chave: diques clásticos; Formação Corumbataí; paleossismologia; nordeste da Bacia Sedimentar do Paraná; Permo-triássico.
Clastic dikes in the Corumbataí Formation, northeastern of the Paraná Basin, State of São Paulo, Brazil: Systematic analysis and stratigraphic, sedimentological and tectonic meanings
Keywords: Clastic dikes; Corumbataí; Formation; Northeast portion of the Paraná; Paleoseismology; Permian-Triassic; Sedimentary Basin; clastic dike; diagenesis; geological survey; igneous intrusion; Mesozoic; outcrop; paleoseismicity; Permian; sedimentary basin; sedimentology; stratigraphy; tectonics; Triassic; Brazil; Corumbatai Basin; Parana Basin; Sao Paulo [Brazil]; South America